1. Fe + H 2 SO 4 → FeSO 4 + H 2

  2. 2Fe + 3H 2 SO 4 → Fe 2 (SO 4 ) + 3H 2

  3. 2Fe + 3H 2 SO 4 → Fe 2 (SO 4 ) 3 + H 2

  4. 2Fe + H 2 SO 4 → Fe 2 (SO 4 ) 3 + 3H 2

 

Answer

  1. Fe + H 2 SO 4 → FeSO 4 + H 2
  1. Class 10
  2. Chapter 1 Class 10 - Chemical Reactions and Equations (Term 1)

About the Author

CA Maninder Singh's photo - Founder at Teachoo
CA Maninder Singh
CA Maninder Singh is a Chartered Accountant for the past 11 years and a teacher from the past 11 years. He teaches Science, Accounts and English at Teachoo